Development of problems for problem-based learning approach in OB-GYN residency training programs in the Philippines - Ocampo-Andres, Imelda S.
Problem-based Learning (PBL) has become, in recent years, the major innovation in most medical curriculum all over the world. Though starting in universities of more developed countries like the McMaster Medical School in Ontario Canada University in the 1960s and the University of Maastricht in the Netherlands in Europe in the 1970s, it soon gained a lot of following in several other countries in the Northern Americas, Australia and later on, the Philippines. In the Philippines, the Association of Philippine Medical Schools was one of the first to accept the challenge. Many educators believe that the PBL is an important approach that could bring deeper learning and would eventually come out with better doctors serving our country. In the same token, the Philippine Obstetrical and Gynecological Society through its academic arm accepted, likewise, the challenge and ventured to adopt this new teaching/learning approach in the implementation of its training programs in our country. The overall objective of this paper is to develop problems using the PBL approach for OB-GYN Training Programs all over the country. This sample problem would serve as model or guide in preparing problems for other topics in the future. VAGINAL BLEEDING, a very common problem obstetrician-gynecologists meet in their everyday practice, served as the topic for which concept maps were made. Although the concept maps varied, the general approach was congruent with each other. These concept maps were used to make 'trigger' cases and formulate objectives for VAGINAL BLEEDING. The next step was to pretest these 'trigger' cases to would-be OB-GYN Residents to find out if the cases made were successful in attaining the objectives for which they were made for in the first place. Towards the ends, recommendations were suggested for the successful adoption and implementation of the PBL approach in the OB-GYN Residency Training Program in the Philippines. Understandably, this is just the first step. But, this is a big leap in the OB-GYN Residency Training Program in the Philippines.